What do drug monopolies cost consumers in developing countries? - Rebecca Hellerstein (Federal Reserve Bank of New York, 2011)
This paper quantifi es the effects of drug monopolies and low per-capita income on pharmaceutical prices in developing economies using the example of the antiretroviral drugs (ARVs) used to treat HIV.
Keywords: D4; F13; L1; L65; O34; 330; intellectual property rights; international price discrimination; TRIPS agreement; pharmaceutical industry; markups